PERBANDINGAN PENYELESAIAN SENGKETA PERUSAHAAN MELALUI LITIGASI DAN NON LITIGASI: PERSPEKTIF PERLINDUNGAN HUKUM HAK ASASI MANUSIA - Mona Wulandari; Desni Raspita; Hendra Apriyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
Rapid societal advancement inevitably gives rise to disputes. Dispute resolution efforts can be pursued through two avenues: litigation and non-litigation. Non-litigation options include deliberation, mediation, and arbitration. Court-based resolution (litigation) is often time-consuming and costly, frequently resulting in one satisfied party and one dissatisfied party. Conversely, non-litigation methods such as mediation, negotiation, or arbitration are considered more efficient and better at preserving relationships between the disputing parties. This study employs a normative-juridical research method. The findings indicate that, despite the shortcomings inherent in the judicial process, the judiciary must be maintained as a